A novel design method for Blass matrix beam-forming networks. - Mosca, S. (IEEE Transactions on antennas and propagation)
A novel design method for lossy Blass matrix beam-forming networks (LBNMFNs) is presented. Compared to those formerly developed, the new method allows the design of an LBMBFN in order to generate not only two simultaneous beams but also an arbitrary number of them. This skill is obtained by means of a new approach to minimize losses that allows one to transform a nonlinear multivariable programming problem into a linear one-variable problem. The solution of such a design problem, then, can be carried out in a very straightforward way by applying Gram-Schmidt orthogonalization. Such a design method takes into account also the limited availability of coupling values of directional couplers. Numerical results obtained through the application of such a design method are then presented. The ease, accuracy, and efficiency of this novel method for the design of LBMBFN make it very useful in modern applications of multibeam antenna arrays